L’argumentaire politique entre effectivité et effets territoriaux : essai sur la viabilité territoriale en espace intermédiaire. - Anthony Merle (L'Espace Politique)
Located in Savoy, in a space that could be described as an "intermediary space", the Lake of Aiguebelette is the object of patrimonial politics since the creation of the Avant Pays Savoyard’s Syndicat mixte in 1985. We suggest, from the case of the Lake of Aiguebelette, an attempt of modelling of the links between political argument, territorial effectiveness and territorial effects in the perspective to emerge a explanation - certainly partial - of what makes the viability of the political territories, especially in these spaces so-called "intermediaries".